Report of metastatic ileal neuroendocrine tumor to the submandibular gland. (2018) - Forner, David; Cho, Peter; Bullock, Martin; Rayson, Daniel; Taylor, S. Mark; Hart, Robert D.; Trites, Jonathan R.; Rigby, Matthew H.
Highlights: The differential diagnosis for neck masses is broad and includes neoplastic, infectious, and anatomic considerations. Bronchopulmonary neuroendocrine tumors are known to metastasize to the head and neck. This report is the first of ileal neuroendocrine tumor metastasis to the submandibular gland. Abstract: Background: Neuroendocrine tumors (NETs) of small intestinal origin are generally slow-growing tumors with a relatively high propensity for metastases to surrounding organs and lymphatic tissue. We present the first case of an ileal NET metastasizing to the submandibular gland in a woman with metastatic carcinoid syndrome. Case presentation: A 55-year-old female presented with a four-month history of a palpable, left-sided neck mass. The patient had a history of metastatic neuroendocrine tumor of ileal origin, initially treated with primary resection 4.5 years previously, with known subdiaphragmatic metastases to the liver, mesenteric nodes, and peritoneum. Four years following primary resection she developed carcinoid syndrome leading to therapy with radiolabelled metaiodobenzylguanidine (MIBG), as well as telotristat etiprate in the context of a clinical trial due to progressive symptoms. A fine needle aspiration biopsy of the neck mass revealed an immunohistochemical staining pattern consistent with ileal NET. The patient underwent a left level 1b neck dissection and submandibular gland excision. Pathology was consistent with metastastic ileal NET. Conclusion: We report the first case of ileal NET metastasis to the submandibular gland. Familiarity with the carcinoid syndrome and associated physiology should be maintained as it can affect the head and neck on rare occasions. Maintaining a broad differential is key in diagnosis of undifferentiated neck masses.